2017
DOI: 10.1007/s12671-017-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

When Traits Match States: Examining the Associations Between Self-Report Trait and State Mindfulness Following a State Mindfulness Induction

Abstract: Previous research has found inconsistent relationships between trait mindfulness and state mindfulness. To extend previous research, we sought to examine the unique associations between self-report trait mindfulness and state mindfulness by levels of meditation experience (meditation-naïve vs. meditation-experienced) and by mindfulness induction (experimentally induced mindful state vs. control group). We recruited 299 college students (93 with previous mindfulness meditation experience) to participate in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 31 publications
2
48
1
Order By: Relevance
“…In this study, previous meditation experience did not interact with the mindfulness-based addiction treatment that was delivered; however, it is plausible that previous meditation experience could have a significant impact on the effects of brief meditation. On the other hand, other recent research suggests that there may be rather weak associations between trait mindfulness and induced mindfulness states (Bravo, Pearson, Wilson, & Witkiewitz, 2018). Thus, previous meditation experience and levels of trait mindfulness may moderate the impacts of mindfulness inductions.…”
Section: Previous Meditation Experience and Motives For Meditationmentioning
confidence: 99%
“…In this study, previous meditation experience did not interact with the mindfulness-based addiction treatment that was delivered; however, it is plausible that previous meditation experience could have a significant impact on the effects of brief meditation. On the other hand, other recent research suggests that there may be rather weak associations between trait mindfulness and induced mindfulness states (Bravo, Pearson, Wilson, & Witkiewitz, 2018). Thus, previous meditation experience and levels of trait mindfulness may moderate the impacts of mindfulness inductions.…”
Section: Previous Meditation Experience and Motives For Meditationmentioning
confidence: 99%
“…Moreover, they reported that change in SMS scores was significantly correlated with reductions in anxiety (Beck & Steer, 1990; r = -.569, p < .001); and depression (Beck, Steer, & Brown, 1996;r = -.355, p < .05) symptoms. Finally, Bravo et al (2018) found that a brief mindfulness exercise (i.e., focused on bodily sensations and the breath) elicited higher SMS Body sub-scale scores (F(1,297) = 18.39, p < .001, partial η 2 = .06), but not SMS Mind sub-scale scores (F(1,297) = 1.14, p = .29, partial η 2 = .00).…”
Section: State Mindfulness Scale (Sms) 12mentioning
confidence: 90%
“…Likewise, participants who reported that they practiced meditation "weekly" or "almost every day" displayed higher SMS scores compared those who practiced "sometimes", had only "tried" meditation, or had never practiced (t93 = 2.64, p = .01, d = .543). Bravo et al (2018) found that:…”
Section: State Mindfulness Scale (Sms) 12mentioning
confidence: 99%
See 2 more Smart Citations